TElomeric repeat-containing RNA (TERRA): Physiological functions and relevance in cancer - Kroupa, Michal; Tomasova, Kristyna; Kavec, Miriam; Skrobanek, Pavel; Buchler, Tomas; Kumar, Rajiv; Vodickova, Ludmila; Vodicka, Pavel (Frontiers in Oncology, 2022)
Telomeres are complex protective structures located at the ends of linear eukaryotic chromosomes. Their purpose is to prevent genomic instability. Research progress in telomere biology during the past decades has identified a network of telomeric transcripts of which the best-studied is TElomeric Repeat-containing RNA (TERRA). TERRA was shown to be important not only for the preservation of telomere homeostasis and genomic stability but also for the expression of hundreds of genes across the human genome. These findings added a new level of complexity to telomere biology. Herein we provide insights on the telomere transcriptome, its relevance for proper telomere function, and its implications in human pathology. We also discuss possible clinical opportunities of exosomal telomere transcripts detection as a biomarker in cancer precision medicine.